Ruminal Metabolism of Soluble Nitrogen in Dairy Cows : Doctoral Dissertation - Stefański, Tomasz (Natural Resources Institute Finland, 2020)
This work focuses on studying rapeseed meal (RM) protein degradation and utilization in dairy cows. Rapeseed meal was selected as a source of protein as it is widely used and cultivated in the European Union, and can be used to replace soybean meal in the rations of lactating dairy cows. This thesis comprises three experiments. Two experiments were conducted using in vitro and in vivo techniques. The objectives of the work were to establish an in vitro method to study protein metabolism in the rumen (Publications I and II), to study the metabolism of ammonia N and soluble fractions of RM protein in vivo (III), and to study the efficiency of utilization of different N fractions for milk protein synthesis (IV). The in vitro experiment documented in publication I involved a preliminary study to develop a mixture of carbohydrates to ensure high proteolytic activity and constant microbial N synthesis over the entire in vitro incubation period. In the main trial, the in vitro method was established to study the rate of ruminal degradation of RM protein based on observations of 14N and 15N isotope fluxes between ammonia N and non-ammonia N pools. In this study, feed protein was incubated with rumen fluid, mineral buffer and a carbohydrate mixture. The ammonia N pool was labelled with 15N isotope, and the incubations were carried out for 10 h with 11 sampling times. The rate of RM degradation estimated with a six-pool model was 0.06/h with an effective protein degradation of 0.38. This approach of studying protein degradation in vitro seemed to be appropriate for determination of microbial N synthesis from ammonia N but it did not provide sufficient information on metabolic events involved in ruminal protein degradation and microbial protein synthesis from preformed amino acids. A novel in vitro method developed to study the metabolism of soluble RM protein was presented in Publication II. In this experiment, unlabelled and 15N labelled soluble fractions of RM were incubated for 10 h with 11 sampling times along with buffered rumen fluid and a carbohydrate mixture. A four-pool model involving pools of 14N and 15N isotopes of ammonia N, soluble non-ammonia N, and insoluble-N from unlabelled and 15N labelled soluble RM incubations was used to estimate parameter values. The mean rate of soluble RM protein degradation was 0.126/h. There was no substantial difference in the rate of protein degradation and microbial N synthesis between the unlabelled and 15N labelled soluble RM. In conclusion, combined data from incubations of unlabelled and 15N labelled soluble RM provided sufficient information for estimation of parameter values in a complex dynamic model of soluble protein degradation. The results also indicated ruminal escape of soluble protein. The ruminal in vivo metabolism of 15N labelled ammonia N and a soluble N fraction of 15N labelled RM protein introduced into the rumen were presented in Publication III. Four lactating dairy cows equipped with rumen cannulae were used in this study. The cows consumed a total mixed ration (60% of silage and 40% of concentrates on DM basis) with 15.5% of crude protein on DM basis, with average rumen ammonia N concentration of 5.5 mg/100mL. The metabolism of ammonia N occurred at a very fast rate, with 99.4% of the original dose disappearing from the ammonia N pool in 4 h. The ammonia N was mainly incorporated into microbial N as 69% of the 15N labelled ammonia N dose disappeared from the rumen as microbial N. In the metabolism of soluble RM protein two steps were observed: 1) an almost instant uptake of more than half of the soluble non-ammonia N (SNAN) dose by the rumen bacteria 2) followed by slower degradation rate of the remaining fraction of the soluble RM protein. It was estimated that 8% of the soluble RM protein N escaped the rumen as feed N. SNAN had a higher initial uptake of the dose than ammonia N (AN) (56 vs. 16%). Also, the outflow as non-ammonia N from the rumen was higher for the SNAN than for AN treatment (89 vs. 69%). More N disappeared (outflow and absorption) from the rumen as ammonia N for the AN treatment than for SNAN treatment (31 vs. 11%). These observations suggested that SNAN was better utilized in the rumen than AN. Higher outflow of microbial N for the SNAN than for AN treatment (81 vs. 69%) indicated that preformed AA and small peptides stimulated microbial growth. The efficiency of utilization of AN, soluble and insoluble fractions of RM protein N for milk protein synthesis were described in Publication IV. The average efficiency of N utilization for milk protein synthesis (milk N/N intake) in this study (32%) was in the higher end of the range reported in the literature (typically from 14% to 36% but in some cases up to 45%). The cumulative secretion of isotope 15N in milk at 108 h post dose indicated that the three studied N fractions had different efficiency of N utilization for milk protein synthesis. The lowest efficiency of N utilization was estimated for AN (19%), followed by the soluble RM fraction (20%), and the highest efficiency of N estimated for the insoluble RM fraction (22%). These differences were smaller than could be expected based on the current protein evaluation systems.
Keywords: dairy cows; soluble protein metabolism; ammonia; isotope 15N; rapeseed; efficiency of utilization of N for milk protein synthesis